A physiologist observing and reporting supra-pharmacologic dobutamine stress testing: can we trust them, and can we trust the results? - Porter, Thomas R (Echo Res Pract, 2018)
In a study, published in this issue of Echo Research and Practice, Ntoskas et al. retrospectively analyzed the safety of a cardiac physiologist performing, and interpreting, Dobutamine stress echocardiography (DSE) in of 300 patients undergoing DSE for the detection of inducible reversible ischemia, myocardial viability and valvular heart disease. While safety during the tests themselves did not appear to be compromised with this unsupervised approach, the interpretation of these DSEs causes concerns regarding broad patient safety relative to misread results.